(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Many industrial heating operations still use fuel oil for combustion instead of the cleaner gaseous fuels. In the steel industry, large furnaces referred to as reheat furnaces are used to heat steel stocks to rolling temperatures using normally fuel oil for combustion. The combustion products of flue gases consist of mainly carbon dioxide, water vapor and traced of other oxides such as nitrogen and sulfur oxides. These oxides are of a concern to the environment and should be minimized as much as possible. Experiments were carried out on a steel billet reheat furnace in which air/fuel ratios are varied while the nitrogen oxide content is being monitored using furnace instruments. These variations in air/fuel ratios for combustion are found to affect the concentration of nitrogen oxides in the flue gas where higher air/fuel ratios promoted the formation of higher nitrogen oxides during combustion. The sulfur dioxide content in the flue gas was calculated based on actual measurements of air and fuel rates to the furnace and found to be minimal in the flue gas.